Stoichiometry of the Cre recombinase bound to the lox recombining site. - Mack, A (1992)
The site-specific recombinase Cre from bacteriophage P1 binds and carries out recombination at a 34 bp lox site. The lox site consists of two 13 bp inverted repeats, separated by an 8 bp spacer region. Both the palindromic nature of the site and the results of footprinting and band shift experiments suggest that a minimum of two Cre molecules bind to a lox site. We report here experiments that demonstrate the absolute stoichiometry of the Cre-lox complex to be one molecule of Cre bound per inverted repeat, or two molecules per lox site.